OPPORTUNITIES, CHALLENGES, AND ETHICAL CONSIDERATIONS OF QUANTUM COMPUTING IN TECHNOLOGY AND BUSINESS - Karimov , Madjit Malikovich; Tashev, Komil; Safoev , Nuriddin (Innovative Development in Educational Activities, 2023)
This paper extensively explores the realm of quantum computing, a revolutionary force set to transform the landscapes of technology and business. Beginning with an in-depth analysis of its fundamental principles, the document delves into the broad-reaching consequences of quantum algorithms, particularly their influence on existing cryptographic methods. Simultaneously, it uncovers substantial opportunities across vital sectors such as finance, healthcare, and logistics. The narrative then scrutinizes the emergence of innovative business models, exemplified by Quantum-as-a-Service (QaaS) and enhanced AI capabilities. While showcasing numerous possibilities, the paper also confronts the challenges and ethical considerations associated with the swift rise of quantum technologies. Emphasizing the necessity for collaborative endeavors among businesses, policymakers, and technologists, the article advocates for a measured and responsible approach to the adoption of quantum technologies.